Formulative policy for managing marine and fishery resources in the management of destructive fishing (Case study of the fisheries and marine services of north maluku province) - Faisal Faisal; Jamal Hi Arsad (Faculty of Law, Khairun University, 2022)
This study aims to analyze and examine the design of formulative policies for handling marine and fishery resources in overcoming the criminal act of destructive fishing in North Maluku and to find out the functionalization of the fisheries and marine service of North Maluku Province in overcoming the crime of destructive fishing. This research is an empirical legal research. The technique of collecting data in this research is through library research and field studies, namely conducting interviews. The results show that the design of formulative policies for handling marine and fishery resources in overcoming the criminal act of destructive fishing in North Maluku implies the need to restore the function of criminal law as the ultimum remedium. These alternative sanctions can be in the form of action sanctions that lead to social, economic improvements, and repairs to damage to fish resources and their ecosystems due to destructive fishing practices. Thus, as one of the fisheries crime that is rife in North Maluku, it must be minimized through partnerships forged by stakeholders in the marine and fisheries sector as well as coastal communities.